A novel optical fiber temperature sensor with polymer-metal alternating structure. (July 2019) - Chou, Yen-Lung; Wu, Chao-Wei; Jhang, Ruei-Ting; Chiang, Chia-Chin
Highlights: A novel polymer-metal alternating structure (PMAS) temperature sensor is proposed. A PMAS temperature sensor based on the LIGA-like process. The sensitivity of this sensor can reach −0.541 nm/℃. The PMAS temperature sensor possesses superior temperature cycle repeatability. Abstract: This paper presents a polymer-metal alternating structure (PMAS) optical fiber temperature sensor fabricated using the LIGA electroforming process; the resulting sensor is a new metal-based optical fiber long-period grating temperature sensor. A periodic s-shaped photoresist structure was patterned onto the etched optical fiber, and the electroforming process was used to deposit nickel within the patterned cavity of the photoresist structure. Due to the thermal expansion of the nickel and the strain-optic effect, when the PMAS sensor is heated, the periodic nickel structure on the optical fiber will induce an expansion strain field in the longitudinal direction of the PMAS optical fiber sensor. The temperature experimental results showed that the resonant wavelengths of the PMAS optical fiber sensor exhibited red shifts as the temperature increased from 60 °C −100 °C. The sensitivity of the sensor to changes in temperature in terms of its wavelength shift was −0.541 nm/°C and R 2 was 0.937. Therefore, the PMAS optical fiber sensor can be applied for temperature measurements.